Capability and need: A framework for understanding why states create sovereign wealth funds. (28th January 2019) - Eldredge, Cody D.
Abstract: Over the past half‐century, roughly one‐quarter of states in the international system have created sovereign wealth funds (SWFs). As a case of sovereign states investing public wealth mostly in private markets across borders, it is not altogether clear why SWFs have proliferated to this extent. What explains their spread in recent decades? In this paper, I build on a multidisciplinary literature that conceives of SWFs as a type of insurance against external risk and argue that middle economic powers that are highly exposed in global trade and capital markets are the states most likely to establish these institutions. Such states possess both the capability to create an SWF of a size sufficient to insure against risk and the need for the insurance function of a SWF by virtue of their relatively vulnerable position in the global economy. To evaluate my argument, I rely on a data set consisting of all states in the international system from 1950 to 2012 including the 48 SWFs created during that period. I find that middle economic powers with high degrees of trade and capital openness are the states most likely to create SWFs.